Implementation of the Concept of Mahabbah (Affection) from the Perspective of Ibn Kathir's Tafsir: A Study on Surah Maryam Verse 96 - Halimatus Sa’diyah; Muthoifin Muthoifin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The focus of this research is to analyze the concept of mahabbah (Affection) in a normative theological manner in Surah Maryam verse 96 according to the view of Tafsir Ibn Kathir. The method used in this study is a qualitative method and library research, data analysis method by analyzing Ibn Kathir's view of the affection stated in the letter Maryam verse 96. The results show that Allah will instill compassion in the hearts of his fellow servants who believer, piety, and do good (good deeds). People who truly believe and do good deeds will get mahabbatullah (Affection) and will be placed in a high place and the best position.